Pressure‐ and heat‐induced protein unfolding in bacterial cells: crowding vs. sticking. Issue 8 (22nd March 2018) - Chen, Timothy; Dave, Kapil; Gruebele, Martin
Abstract : In‐cell protein stability is increased by crowding, but can be reduced by destabilizing surface interactions. Will different denaturation techniques yield similar trends? Here, we apply pressure and thermal denaturation to green fluorescent protein/ReAsH‐labeled yeast phosphoglycerate kinase (PGK) in Escherichia coli cells. Pressure denaturation is more two state‐like in E. coli than in vitro, stabilizing the native state. Thermal denaturation destabilizes PGK in E. coli, unlike in mammalian cells. Results in wild‐type MG1655 strain are corroborated in pressure‐resistant J1 strain, where PGK is less prone to aggregation. Thus, destabilizing surface interactions overcome stabilizing crowding in the E. coli cytoplasm under thermal denaturation, but not under pressure denaturation. Abstract :